Neoadjuvant chemoradiation versus adjuvant chemotherapy for locally advanced adenocarcinoma of the rectosigmoid junction. (20th December 2019) - Salami, A. C.; Obaid, T.; Nweze, N. J.; Deleon, M.; Force, L.; Gorgun, E.; Wexner, S.; Joshi, A. R. T.
Abstract: Aim: The optimal treatment approach for adenocarcinoma of the rectosigmoid junction remains unclear. The aim of this work was to compare outcomes of neoadjuvant chemoradiation (NCR) and adjuvant chemotherapy (AC) treatment for cancer of the rectosigmoid junction. Method: This was a nationwide, retrospective cohort study (2004–2015) using hospital‐based cancer outcomes data (National Cancer Database). All patients who underwent resection with curative intent for locally advanced [American Joint Committee on Cancer (AJCC) Stages II and III] adenocarcinoma of the rectosigmoid junction were included. Exclusion criteria were age less than 18 or over 75 years, Charlson–Deyo score > 2, AJCC Stages I and IV and unstaged tumours. Treatment with NCR was compared with treatment with AC, the primary outcome being overall survival. Other end‐points were resection margin status, the presence of lymphovascular invasion and postoperative length of stay. Results: A total of 2828 patients were included in this study, of whom 1701 (59.7%) received NCR. NCR was more frequently utilized in patients who were black (10.3% vs 7.6%, P  < 0.05) and underwent treatment at academic institutions (37.9% vs 22.5%, P  < 0.05). Treatment with NCR did not differentially influence survival following risk adjustment (hazard ratio 1.17, CI 0.98–1.40; P  = 0.085). NCR was independently associated with a decreased likelihood of a positive resection margin (OR 0.44, CI 0.33–0.58; P  < 0.001) and lymphovascular invasion (OR 0.51, CI 0.40–0.67; P  < 0.001). However, treatment with NCR was associated with the need for prolonged hospitalization compared with AC (7.3 days vs 6.5 days; P  = 0.015). The study was limited by its retrospective design, external validity and risk of tumour misclassification. Conclusion: NCR currently seems to be favoured over AC for the management of locally advanced adenocarcinoma of the rectosigmoid junction. This approach may not be justified as NCR is associated with prolonged hospitalization needs without a clear survival benefit when compared with AC. Prospective studies are warranted to definitively compare outcomes of NCR and AC in this patient population.